ANALISIS MODEL KEBUTUHAN PARKIR PADA BANGUNAN PERDAGANGAN DI KOTA BANJARMASIN - Rosehan Anwar (INFO-TEKNIK, 2005)
Parking area is one of the important problem in our daily life.  This park problem increases as much as growth of resident.  As the increasing of amont of people and vehicle. Those wildings are no longer enable to provide the parking area, beside that buldings with many space parking area. The purpose of this research is describing the need of two and four wheel vehicle for the parking area in the comerse building inBanjarmasin. In this case, providing of parking area is counting based on the maximum accumulation of two and four wheel vehicle to the width of building, amount of employees.The method used is analysis of linier and multy linier regresi.  As the result of analysis, the best regresi model for four wheel motor vehicle parking is linier with equition of  Y1 = 4,63 + 0,0083  X1  With  R2 = 0,981, and for two wheel motor vehicle is linier with equition of  Y2 = 2,84 + 0,0167 with R2 = 0,982.  The minimum standart widw of parking need four for the four wheel motor vehicle is one check park 101 m2 of comerce building, and for the two wheel motor vehicle is one check park  57 m2 of comerce building.